“Des personnages de si près tenus”, TV Fiction and Moral Consensus - Chalvon-Demersay, Sabine (Qualitative Sociology Review, 2007)
How can we understand the adaptations of literary classics made for French television? We simultaneously analyzed the works and the context in which they were produced in order to relate the moral configurations that emerge in the stories to activities carried out by identifiable members of the production team, in specific, empirically observable circumstances. This empirical approach to the constitution of the moral panorama in which characters evolve rejects the idea of the pure autonomy of ideological contents, suggesting instead a study of the way normative demands and professional ethics are combined in practice, thus combining a sociology of characters and a sociology of professionals and showing how professional priorities influence production choices. This detaches the moral question from the philosophical horizon it is associated with in order to make it an object of empirial study. Adopting this perspective produces unexpected findings. Observation shows that the moral landscape in which characters are located is neither stable, autonomous, transparent, or consensual. It is instead caught up in material logics, constrained by temporal dynamics, and dependent on professional coordination. It is traversed by tensions between professional logics, and logics of regulation.